Collective energy actions to pursue a just transition. - Martina Massari; Saveria Olga Murielle Boulanger; Danila Longo (European Journal of Spatial Development, 2024)
The EU recent energy policies aim to rapidly transition to a sustainable and citizen-centric energy system. However, most regulations do not fully acknowledge the social aspect of the energy transition. The relationship between collective energy action (energy citizenship) and the just transition framework requires further examination. This paper aims to explore the relationship between just transition and energy citizenship in Southern European collective energy actions, showcasing their association and varied impacts based on agency dynamics, contextual factors, and governance models. It also proposes new tools and analytical lenses to assess and govern place-based collective energy actions, complementing policy-making efforts.